2021
DOI: 10.1158/1078-0432.ccr-21-0706
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Intratumoral Molecular Heterogeneity in Clear Cell Renal Cell Carcinoma with a Radiogenomics Platform

Abstract: ◥Purpose: Intratumoral heterogeneity (ITH) challenges the molecular characterization of clear cell renal cell carcinoma (ccRCC) and is a confounding factor for therapy selection. Most approaches to evaluate ITH are limited by two-dimensional ex vivo tissue analyses. Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) can noninvasively assess the spatial landscape of entire tumors in their natural milieu. To assess the potential of DCE-MRI, we developed a vertically integrated radiogenomics colocaliz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Similarly, Xi et al reported the larger area of high Gd-enhanced k-means cluster within a tumour to be most predictive of higher grade across a cohort of 18 patients with T1b ccRCC 48 ; however, these results relied on a single postsurgical grade for the whole tumour rather than examining grade variation across the entire tumour. Udayakumar et al correlated the intratumoral variation in early nephrogenic enhancement with angiogenic and immune transcriptomic signatures of biopsies the same regions 49 and Yao et al reported two types of microvessels which are differentially expressed between low and high grade ccRCCs, indicating the complexity of ccRCC perfusion 50 . These results indicate that tumour perfusion is an important determinant of aggressiveness but used alone is insufficient to fully and accurately characterise the tumour grade non-invasively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Xi et al reported the larger area of high Gd-enhanced k-means cluster within a tumour to be most predictive of higher grade across a cohort of 18 patients with T1b ccRCC 48 ; however, these results relied on a single postsurgical grade for the whole tumour rather than examining grade variation across the entire tumour. Udayakumar et al correlated the intratumoral variation in early nephrogenic enhancement with angiogenic and immune transcriptomic signatures of biopsies the same regions 49 and Yao et al reported two types of microvessels which are differentially expressed between low and high grade ccRCCs, indicating the complexity of ccRCC perfusion 50 . These results indicate that tumour perfusion is an important determinant of aggressiveness but used alone is insufficient to fully and accurately characterise the tumour grade non-invasively.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have found that inflammatory cells and factors play an important role in the development, transformation and metastasis of tumors, including inflammatory cells, chemokines, their receptors and downstream signaling pathways 31–34 . ccRCC is a typical immunogenic tumor with abundant immune cell infiltration 35 .…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29][30] In recent years, many studies have found that inflammatory cells and factors play an important role in the development, transformation and metastasis of tumors, including inflammatory cells, chemokines, their receptors and downstream signaling pathways. [31][32][33][34] ccRCC is a typical immunogenic tumor with abundant immune cell infiltration. 35 Immunogenicity, the ability to induce an adaptive immune response, is determined by tumor antigens, extent of immune cell infiltration and type and number of immunomodulatory molecules emerging in the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Effective therapeutic strategies suppressing RCC progression are still limited. The intratumor cellular heterogeneity or distinctive molecular characteristics dictates the main challenges [ 30 , 31 ]. Hypoxia signaling is a well-investigated contributor to RCC that drives tumor growth or metastasis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%